Relação civil militar na Guiné-Bissau (2000-2020) - Bissindé , Cam-Naté Augusto (2024)
Given a context of extreme political, economic and social instability in Guinea-Bissau, it is intended, through this dissertation, to study the cycles of interventions of the Armed Forces in everyday political life over the last two decades. The work seeks to study, deliberately, how the successive blows took place, and what impacts the society reaped. The work is divided into three parts, in addition to the introduction and final considerations. In the first part, some concepts related to the theme of civil-military relationship are addressed, to bring together the thought of experts on the subject and dialogue about the approaches they present. In the second part, the emphasis is on the historical contextualization of the formation of the Armed Forces of Guinea-Bissau in a context marked by the national liberation struggle against Portuguese colonialism. The third and final part deals specifically with the 2014 general election, analyzing the expectations and political frustrations marked by the political-party crisis. Also in the last part was made the analysis of interviews.